Integrated stratigraphy of the St. Thomas section (Malta Island): A reference section for the lower Burdigalian of the Mediterranean Region - Foresi, L. M.; Baldassini, N.; Sagnotti, L.; Lirer, F.; Di Stefano, V; Caricchi, C.; Verducci, M.; Salvatorini, G.; Mazzei, R. (Marine Micropaleontology, 2014)
The 91.15 m thick St. Thomas section belongs to the Middle Globigerina Limestone, which is the intermediate member of the Globigerina Limestone Formation, and crops out along the eastern cliff of the Delimara Peninsula (the south-eastern part ofMalta Island). The sedimentary record is composed of alternating calcareous marls and marly limestones with subordinated prominent bioturbated indurated limestones that are deposited in a pelagic environment. For the first time paleomagnetic analyses of a Burdigalian succession have provided reliable data that allow the identification of five magnetozones that have been correlated to the Astronomically Tuned Neogene Time Scale, spanning the Early Miocene C6n–C5Dn interval. Calcareous plankton quantitative analyses integrated with paleomagnetic analyses, allowed us to identify and date several bioevents that have great potential for Mediterranean and extra-Mediterranean correlations in the interval between ~19.7 and ~17.2 Ma. In particular, the complete distributional range of the calcareous nannofossil Sphenolithus belemnos has been recorded as follows: the First Occurrence (FO) at 19.12 Ma, the First Common Occurrence (FCO) at 19.05 Ma, the Last Common Occurrence (LCO) at 18.44 Ma, and the Last Occurrence (LO) at 18.02 Ma. In addition, the FO and the FCO of Sphenolithus heteromorphus have been documented at 18.29 Ma and at 17.99 Ma, respectively. A new paracme interval in the lower part of the range of this species is described between 17.56 and 17.31 Ma. Concerning the planktonic Foraminifera, the main bioevents are the Common Interval top of Paragloborotalia siakensis at 19.55 Ma, a Common Interval of Globoquadrina dehiscens between 19.34 and 18.48 Ma, the Globigerinoides subquadratus FO at 18.43 Ma, and the onset of an acme interval of Paragloborotalia acrostoma that changes its coiling from random to prevalently sinistral at the same time, at 18.40 Ma. These new biostratigraphic data allowed us to place the succession in the standard Mediterranean calcareous plankton ...